Implementation of Blockchain Technology to Enhance the Security of Online Payment Transactions - Ariesya Aprillia; Denok Wahyudi Setyo Rahayu; Arista Ratih; Thomas Green (IAIC Bangun Bangsa, 2026)
The rapid growth of digital financial services has significantly increased the volume of online payment transactions, while simultaneously intensifying concerns related to transaction security, data integrity, privacy protection, and fraud due to the limitations of centralized payment architectures, which remain vulnerable to cyberattacks, data manipulation, and single points of failure. This study aims to analyze the role of blockchain technology in enhancing the se- curity of online payment transactions by examining its core characteristics, including decentralization, transparency, immutability, and smart contracts. This research adopts a conceptual and descriptive comparative approach by synthesizing recent peer-reviewed literature to evaluate blockchain-based payment systems in comparison with conventional centralized systems. The findings indicate that blockchain implementation improves transaction security by reducing fraud risks, eliminating single points of failure, ensuring tamperresistant records, and enhancing transparency and traceability, thereby increasing user trust. These improvements contribute to more reliable, transparent, and resilient digital payment infrastructures. Furthermore, blockchain technology supports the SDGs 8 (Decent Work and Economic Growth), SDGs 9 (Industry, Innovation, and Infrastructure), and SDGs 16 (Peace, Justice, and Strong Institutions), by promoting transparency, accountability, and long-term stability in digital financial ecosystems.